Primary Hodgkin Lymphoma lung in a background of congenital pulmonary airway malformation - Sohaila Fatima; Wajih Ahmed Siddiqui; Abdulrahman Alshehri (Elsevier, 2018)
Congenital pulmonary airway malformation (CPAM) is a developmental anomaly of the lower respiratory tract. We document a case of primary Hodgkin Lymphoma of lung occurring in a 13-year-old boy who had an incidental diagnosis of CPAM at the same time. Keywords: Hodgkin lymphoma, Lung, CPAM